Father involvement and men's satisfaction of life - Katarzyna Wac (Kazimierz Wielki University, 2018)
Introduction: The benefits of father involvement for children are widely acknowledged; involved fathers enhance academic success and protect children from improper behavior with benefits that extend far beyond the childhood years (Lamb, 2010; Lamb, Lewis, 2004; Pleck, 1997). Research to date has only just begun to consider another key question: How do parenting roles affect fathers? Purpose of work: The aim of this project is to verify the relationship between men's involvement in paternity and men's satisfaction of life. Specifically, the project aims at answering the following question: whether involvement in paternity is positively related to men's satisfaction of life. Material and method: 100 people - men who are biological fathers, who have at least one child in school or pre-school age (one child aged at least 4 years old but the oldest is no more than 19 years old), first married. Paternity itself is differentiated that is why it is important to keep the homogeneity of the group. The research had a questionnaire character: SWLS scale and a sheet was used. Results: The research confirmed the relation between fatherhood satisfaction and satisfaction of life. Conclusions: Fatherhood is one of the way of men fulfillment understood as a satisfaction of life.